Aromaterapi Lemon Menurunkan Mual Muntah pada Ibu Hamil Trimester I: Lemon Aromatherapy Reduces Nausea Vomiting in First Trimester Pregnant Women - Cholifah, Siti; Nuriyanah, Titin Eka (Universitas Muhammadiyah Sidoarjo, 2018)
Nausea vomiting (Emesis gravidarum) is most commonly complaint occur in pregnant women by 50-90%, with 2% ending into excessive nausea vomiting (hyperemesis gravidarum) that can harm the mother and fetus. One of the safest non-pharmacological therapies to be given to nausea moms of vomiting during pregnancy is lemon aromatherapy. The objective of this study was to know the effect of lemon aromatherapy in decreasing nausea at the first trimester gravid. The method were used in this research is pre experimental with the design of One Group Pre-Post Test Design. The population the first trimester gravida who experienced nausea vomiting using consecutive sampling technique that fulfilled the inclusion criteria amounted to 36 respondents. Data were analyzed by using Wilcoxon Sign Rank Test with α = 0,05. The results showed that the scale of nausea vomiting at the first trimester gravid before giving aromatherapy Mean + SD 23,33 + 3,913 while after giving aromatherapy Mean + SD 13,67 + 4,071. Result of Wilcoxon Sing Rank Test with significance level α = 0,05 got p = 0.0001 (P <α 0,05) then H1 accepted and H0 rejected. Conclusions of the study showed that lemon aromatherapy had significant effect in reducing nausea vomiting in the first trimester gravid. Suggestion for health officer (midwife) can apply alternative therapy of lemon aromatherapy to reduce and overcome nausea vomiting and can be developed for more research about complementary therapy to overcome nausea vomiting.